2014
DOI: 10.1002/met.1480
|View full text |Cite
|
Sign up to set email alerts
|

Communication and interpretation of regional weather forecasts: a survey of the Italian public

Abstract: ABSTRACT:The aim of the present study is to contribute to the correctness and effectiveness of weather forecast communication, the importance of which has been steadily growing along with the improvement in numerical weather prediction models and methods as well as the general awareness about the increase of extreme events within a context of global climate change. An extensive survey was conducted among the general users of the weather forecasts issued by the regional meteorological service of Tuscany, Italy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 35 publications
14
39
0
Order By: Relevance
“…Nonetheless, providing an hourly forecast beyond 7 days and, in general, providing a detailed and localized forecast for a long lead time is not justified; it increases users' expectations about local forecast accuracy and, in the end, undermines the credibility of the science of meteorology. This is true even if several studies (Morss et al , ; Lazo et al , ; Joslyn and Savelli, ; Zabini et al , ) have found that people are aware that the uncertainty in weather forecasts varies with the forecast lead time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, providing an hourly forecast beyond 7 days and, in general, providing a detailed and localized forecast for a long lead time is not justified; it increases users' expectations about local forecast accuracy and, in the end, undermines the credibility of the science of meteorology. This is true even if several studies (Morss et al , ; Lazo et al , ; Joslyn and Savelli, ; Zabini et al , ) have found that people are aware that the uncertainty in weather forecasts varies with the forecast lead time.…”
Section: Resultsmentioning
confidence: 99%
“…The only way that uncertainty is expressed in the study sample is by PoP, generally conveyed in a numerical format (as a percentage probability) (27 of 39 apps contain PoP). Notwithstanding this, users have problems with the interpretation of PoP, as shown in several studies including Murphy et al (1980), Sink (1995), Gigerenzer et al (2005), Handmer and Proudley (2007), Morss et al (2008), Joslyn and Nichols (2009), Joslyn et al (2009a, 2009b, Joslyn and Savelli (2010), Peachey et al (2013), Kox et al (2014), Zabini et al (2015) and Abraham et al (2015).…”
Section: Implications For Communication Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, hundreds of teachers and students took part in the proposed modules, with many of them visiting LaMMA, meeting researchers and increasing their knowledge about meteorology and intrinsic uncertainty of weather forecasts (Zabini, 2016;Zabini et al, 2015). As the evaluation attests, the LaMMA educational modules are appreciated by students who find them engaging and challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The research reported here extends these evaluations by focusing on county emergency managers (EMs) in the United States, local-level professionals who apply management, planning, science, and technology to deal with flooding that can cause property damage, disrupt community life, and kill or injure people (Hoetmer, 1991, p. xvii). Do these first-responder experts face the same kind of decision constraints revealed in other assessments of forecast use in weather-related disasters, almost all of which have examined the general public (see, for example, Joslyn, Nadav-Greenberg, and Nichols 2009;Lazo, Morss, and Demuth, 2009;Joslyn and Savelli, 2010;Joslyn and LeClerc, 2012;LeClerc and Joslyn, 2015;Zabini et al, 2015). Only a small number have concentrated on professionals involved with forecasts, such as the forecasters themselves (Demeritt et al, 2007(Demeritt et al, , 2013Pappenberger et al, 2013), experts interested in using flood visualisation tools (Frick and Hegg, 2011), and emergency service providers (Kox, Gerhold, and Ulbrich, 2015).…”
Section: Introductionmentioning
confidence: 99%